Ginger Extract and [6]-Gingerol Inhibit Contraction of Rat Entire Small Intestine - Usana Chatturong; Tanwarat Kajsongkram; Sakara Tunsophon; Rachanee Chanasong; Krongkarn Chootip (SAGE Publishing, 2018)
This study aims to investigate the effect of oral administration and the direct action of ginger extract or [6]-gingerol on small intestinal contractility. The direct effect of 10 minutes preincubation of ginger ethanolic extract (10, 100 and 300 μg/mL) or [6]-gingerol (1, 30, and 100 μM) on 0.01 to 30 μM ACh-induced contractions of all parts of the small intestine isolated from normal rats was investigated using the organ bath technique. For in vivo study, the rats were orally administered with extract (10, 20, and 100 mg/kg/d) or [6]-gingerol (2 mg/kg/d) for 7 days, followed by determining the contractile responses to ACh of rat isolated duodenum, jejunum, and ileum and their histology were assessed. Direct application of the extract or [6]-gingerol attenuated ACh-induced contractions in each small intestinal segment, E max was reduced by 40% to 80%, while EC 50 increased 3- to 8-fold from control. Similarly, in the in vivo study ACh-induced contractions were reduced in all parts of the small intestine isolated from rats orally treated with ginger extract (20 and 100 mg/kg/d) or [6]-gingerol (2 mg/kg/d). E max decreased 15% to 30%, while EC 50 increased 1- to 3-fold compared to control. No discernable changes in the histology of intestinal segments were detectable. Thus, the results support the clinical application of ginger for disorders of gastrointestinal motility.